The The Relationship between Accessibility of Telemedicine Services and Decisions on Use: A Cross-Sectional Study at X General Hospital Malang - Puspitaning Ayu, Jennyla; Herwati, Ida (POLTEKKES KEMENKES YOGYAKARTA, 2024)
As many as 65% of patients interviewed about telemedicine at Outpatient Hospital X in Malang Regency admitted that they were only aware of telemedicine services like Halodoc, Alodokter, Klikdokter, and the hospital's telemedicine applications, but had never directly used them. The patient acknowledges that the application menu service on several telemedicine platforms is overly complicated and challenging to navigate, particularly for patients over the age of 45. The aim of this study was to determine the relationship between the accessibility of telemedicine service applications and the decision to use them. In January 2023, we conducted this research at the outpatient facility of one of the hospitals in Malang Regency. This study had a total sample size of 67 patients. Researchers gathered the data through a questionnaire utilising a Likert scale, concentrating on the accessibility of telemedicine and the choices made concerning it. Researchers conducted statistical analyses using Pearson correlation. The findings revealed a significant correlation between telemedicine service accessibility and utilisation, with a significance level of 0.000, thereby validating the hypothesis. The decision to employ the telemedicine application for outpatient care is made. The hospital in Malang Regency is influenced by factors such as the ease of communication with health care providers, the clarity of their voices, the provision of diagnoses based on the patient's condition, the patient's ability to clearly see the health care provider or health worker, and the ease of using the telemedicine application itself.